2022
DOI: 10.3892/etm.2022.11162
|View full text |Cite
|
Sign up to set email alerts
|

Total astragalosides decrease apoptosis and pyroptosis by inhibiting enterovirus 71 replication in gastric epithelial cells

Abstract: Enterovirus 71 (EV71) is one of the primary pathogens involved in severe hand, foot and mouth disease in children. EV71 infection causes various types of programmed cell death. However, there are currently no clinically approved specific antiviral drugs for control of EV71 infection. Astragalus membranaceus (AM), a Traditional Chinese medicine, has been used in antiviral therapy in China. The aim of the present study was to determine whether total astragalosides (ASTs), bioactive components of AM, protect agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Moreover, astragalus membranaceus is reported to suppress EV71 replication and protect cells against EV71-induced apoptosis and pyroptosis. [49] Caspase-1 inhibitor suppressed the EV71 replication, IL-1β and IL-18 secretion, and improved the host response during EV71…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, astragalus membranaceus is reported to suppress EV71 replication and protect cells against EV71-induced apoptosis and pyroptosis. [49] Caspase-1 inhibitor suppressed the EV71 replication, IL-1β and IL-18 secretion, and improved the host response during EV71…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, astragalus membranaceus is reported to suppress EV71 replication and protect cells against EV71‐induced apoptosis and pyroptosis. [ 49 ] Caspase‐1 inhibitor suppressed the EV71 replication, IL‐1β and IL‐18 secretion, and improved the host response during EV71 infection. [ 50 ] Similarly, the inhibition of HMGB1 inhibited the activation of NLRP3 inflammasome and pyroptosis in EV71‐infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is a form of death characterized by the appearance of pores in the cell membrane, resulting in changes in the osmotic pressure inside and outside the cell, followed by cell swelling [17,18]. Many infectious diseases point to the necessity of gasdermin family proteins (mainly GSDMD) in pyroptosis [19][20][21]. A related study in a mouse model of JEV infection showed that GSDMD was signi cantly elevated at the transcriptional level, indicating that pyroptosis was involved in viral infection during the period of pronounced clinical symptoms [22].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, growing evidence has been clearly pointed out that pyroptosis exerted an important role in EV-A71 infection ( Wang et al., 2022b ). For instance, EV-A71 infection induced gastric epithelial cells damage by triggering pyroptosis ( Zhang et al., 2022 ). AIM2 inflammasome-mediated pyroptosis in EV-A71-infected neuronal cells restricts viral replication.…”
Section: Discussionmentioning
confidence: 99%